HISTORICAL FEATURES OF THE FORMATION OF SPACE AND ARTISTIC DECORATION OF THE INTERIORS OF CHURCHES IN THE UKRAINIAN PODILLYA REGION - ШТОГРИН, А. М.; ТРЕТЯК, Ю. В. (Art and Design, 2024)
Purpose of the article is to analyze and systematize the historical, cultural, and regional peculiarities of the formation of the interior spaces of Ukrainian churches and their artistic and decorative decoration for the further implementation of the results obtained in the design of new churches and the restoration of destroyed churches. Research methodology is based on the systemic and system-synergetic approaches and is based on the methods of studying and analyzing historical and archival documents, as well as field surveys of Podillia churches. Results of the work are reflected in several features of the formation and decoration of the interiors of historical church buildings of Ukrainian Podillia of the eighteenth and nineteenth centuries, namely: the interior space is well-structured, with major and minor functional zones; the composition of the temple space develops in an ascending manner, has elongated proportions; the presence of a multi-tiered iconostasis in the interior, which is the dominant feature of the composition; the coloristic and plastic solution of the iconostasis reflects local deep cultural, religious, architectural and artistic traditions, which makes the temple space a “place of strength” and unity of the people. These features make it possible to further formulate the principles of composition and decoration of the object-spatial environment of Ukrainian churches. Scientific novelty of the work lies in the historical analysis of the interiors and decoration of churches in Ukrainian Podillia, the identification of the peculiarities of the formation of their object-spatial environment in terms of preserving and restoring the traditions of regional culture, architecture, and art by the challenges of modernity with its new style, innovations, and, in general, a new worldview. Practical significance of the article lies in the possibility of using the research data in the educational and professional design of the subject-spatial environment of church buildings, as well as for understanding the issues of synthesis of fine and plastic arts in their decoration.